PENGETAHUAN TENTANG MEROKOK TERHADAP PERILAKU MEROKOK PADA SISWA DI SMKN 6 KOTA PEKANBARU - Tyagita Widya Sari; Muliana Lestari; Nadia Rukmana; Yogi Ersandy (Jurnal Keperawatan Abdurrab, 2020)
Background: The World Health Organization (WHO) states that smoking causes fatal health problems which cause about 8 million deaths per year worldwide. The risk of death from active smokers is higher than passive smokers, which is about more than 7 million deaths occur in active smokers and 1.2 million deaths occur in passive smokers. The results of the 2018 Basic Health Research report (Riskesdas) showed that the prevalence of smoking among adolescents of school age or aged 10-18 years (both inside and outside school) had increased according to the 2018 Basic Health Research (Riskesdas) which was recorded at 9.1 %, up from Riskesdas 2013 which was 7.2%. Lack of knowledge about smoking will cause teens to be easily influenced by peers. Good knowledge illustrates a broader experience regarding smoking so that it will also affect one's smoking behavior Objectives: To determine the correlation of knowledge about smoking with smoking behavior of students at SMKN 6 Pekanbaru City. Methods: This study used an observational study with a cross-sectional study design. The sampling technique in this study was simple random sampling, where the number of respondents in this research was 149 students. Results: Knowledge about smoking is correlated to smoking behavior of students with a p-value of 0.048 (p-value <0.05) and a weak correlation power with a negative direction (r = -0,162). Conclusion: Knowledge about smoking is correlated to smoking behavior of students at SMKN 6 Pekanbaru City. The lower the students' knowledge about smoking, the worse their smoking behavior will be.